Modifying effect of diabetes mellitus on the dynamics of parameters of free radical process intensity and antioxidant protection activity in the liver of rats with incomplete global cerebral ischemia-reperfusion - Tkachuk, S. S.; Povar, M. A.; Tkachuk, O. V.; Myslytskyi, V. F.; Gavaleshko, V. P. (Journal of Education, Health and Sport, 2018)
According to the WHO expert assessment diabetes mellitus (DM) will take the seventh position among leading causes of death in 2030 [1]. The most dangerous complications of DM becoming a cause of severe disability or mortality are acute cerebral disorders of ischemic genesis [2, 3], which in case of this pathology occur several times more frequently than in case of its absence [4, 5]. The causes of complicated development of cerebral ischemia-reperfusion against the ground of DM are being investigated actively, and pathogenesis of brain damage in case of this comorbid pathology appears to be the most studied, although the mechanisms of morphofunctional disorders of the parenchymal organs remain without attention of researchers, since they are touched upon only in several works [6, 7]. Meanwhile, even short hypoxic conditions of the brain are known to result in considerable pathohistological changes in the internal organs becoming a cause of disorders in their functional state and require correction [7, 8]. The most permanent and long changes occur in the liver even to the destruction of separate cells or their groups [9-11]. These changes in case of cerebral ischemia are initiated due to redistribution of blood flow and oxygen supply in favour of the brain, and therefore partial oxygen pressure in the abdominal organs decreases, and in the liver in particular [10]. From the other hand, metabolic disorders associated with diabetes mellitus are generally known to cause liver damage [12-14], therefore diabetic complications caused by cerebral ischemia-reperfusion should be logically expected to intensify morphofuncitonal changes in the organ. Meanwhile, we have not found investigations of the kind described in the scientific literature yet. Objective and tasks: to examine the signs of oxidative and nitrosative stress in the liver of rats with diabetes mellitus complicated by cerebral ischemia-reperfusion.In the liver of rats without DM 20 minute carotid ischemia with 1 hour reperfusion by the changes of the content of lipid peroxidation products and activity of antioxidant enzymes results in depression of the lipid peroxidation-antioxidant protection system. On the 12th day of observation diene conjugated content increases in the organ against the ground of increased activity of superoxide dismutase and glutathione peroxidase, which in general is indicative of a compensatory reaction character of the system. The indices of protein oxidative modification and nitrogen oxide metabolism in the liver of animals without diabetes at the early post-ischemic period remain unchanged, and on the 12th day of the experiment they increase, which confirms availability of oxidative and nitrosative stress at this period. With DM available reaction of all the above indices in the liver is absent both at the early and late post-ischemic periods, which characterizes a-reactivity of these biochemical parameters concerning cerebral ischemia-reperfusion.